2006
DOI: 10.1016/j.abb.2006.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Traction forces of fibroblasts are regulated by the Rho-dependent kinase but not by the myosin light chain kinase

Abstract: Adhesive cells show complex mechanical interactions with the substrate, however the exact mechanism of such interactions, termed traction forces, is still unclear. To address this question we have measured traction forces of fibroblasts treated with agents that affect the myosin II-dependent contractile mechanism. Using the potent myosin II inhibitor blebbistatin, we demonstrate that traction forces are strongly dependent on a functional myosin II heavy chain. Since myosin II is regulated by both the myosin li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 51 publications
(67 reference statements)
8
97
2
Order By: Relevance
“…Because the bulk of traction forces have been shown to be generated by myosin-II-mediated contractility (Beningo et al, 2006), we expected blebbistatin, a potent inhibitor of myosin II ATPase, to inhibit not only traction forces, but also any increase in traction force upon microtubule depolymerization. Blebbistatin treatment caused a sixfold decrease in average traction stress in patterned cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the bulk of traction forces have been shown to be generated by myosin-II-mediated contractility (Beningo et al, 2006), we expected blebbistatin, a potent inhibitor of myosin II ATPase, to inhibit not only traction forces, but also any increase in traction force upon microtubule depolymerization. Blebbistatin treatment caused a sixfold decrease in average traction stress in patterned cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated a strong dependence of traction forces on myosin II (Beningo et al, 2006;Gardel et al, 2008). Patterning cells allows more precise quantification and has indicated an incomplete inhibition of traction stress upon blebbistatin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, mechanical forces, either generated internally by myosin II or applied externally through focal adhesions, may play a role in inducing the fluxes. Y-27632, an inhibitor of the Rho-dependent kinase, and blebbistatin, an inhibitor of myosin II ATPase, both caused strong inhibition of traction forces (Beningo et al, 2006), and focal adhesion fluxes, while reducing zyxin tails to small dot-like structures (Figure 6, A-C, and Supplemental Movie 6). Conversely, application of pulling forces to cells plated on flexible polyacrylamide substrates stimulated the appearance of focal adhesion fluxes (Figure 6, D-G).…”
Section: Dependence Of Focal Adhesion Fluxes On Cellular Contractilitmentioning
confidence: 99%
“…Cells respond to outside-in signals by exerting actomyosin-based contractile forces on the matrix (inside-out forces) that increase cell stiffness and scale with ECM stiffness [2]. Rho/ROCK signalling is rapidly activated at ECM adhesions in response to matrix stiffness to augment actomyosin activity, via actin polymerisation and myosin light chain phosphorylation, and increase cell stiffness [3,4].…”
Section: Introductionmentioning
confidence: 99%